Post-Dengue Swelling: An Atypical Presentation and Diagnostic Dilemma Resolved with Herbal Decoction - Yousf Mir, Uzair; Adeena Parveen, Shaik; Hamid Wani, Umer; Ahmad Bhat, Ajaz; Sumeena, Sumeena (Journal of Neonatal Surgery, 2025)
Dengue fever is an important arboviral disease, transmitted by mosquitoes especially those of the Aedes genus, primarily by Aedes (Stegomyia) aegypti (Linnaeus, 1762) and in some rare cases by Aedes (Stegomyia) albopictus (Skuse) with a wide clinical spectrum, ranging from self-limiting mild sickness to life threatening conditions like dengue hemorrhagic fever (DHF) and eventually dengue shock syndrome (DSS). In the past decade, the emergence of dengue has been linked to unusual coinfections.The transitory reduction of host innate immunity could be the most likely cause of dengue-associated co-infections and/or super-infections. Furthermore, the dual infection can aggravate the clinical course of dengue fever. We are reporting an unusual case of intramuscular calf swelling in a 27-year-old male patient following dengue.The swelling yielded conflicting radiological interpretations, including intramuscular cysticercosis, cellulitis, abscess and hematoma. This diagnostic ambiguity posed significant challenges in managing the swelling. Despite these diagnostic challenges, the swelling was effectively managed with a herbal decoction made from three Unani herbs: Artemisia absinthium, Swertia chirata, and Tinospora cortifolia.